Thymocyte Differentiation is Regulated by a Change in Estradiol Levels during the Estrous Cycle in Mouse - Lee, Hyojin (Dev Reprod, 2013)
Recent study showed that T cells in the immune organs and peripheral blood are influenced by estradiol, leading to a dysfunction of the immune system. However, little is known about the thymic-gonadal relationship during the estrous cycle in mouse. Therefore, the purpose of this study was to elucidate the mechanism by which a change in estradiol levels during the estrous cycle regulates the development of T cells in the mouse thymus. Six-week-old ICR mice were used and divided into four groups, including diestrous, proestrous, estrous, and metestrous. We first confirmed that ER-α and - β estrogen receptors were expressed in thymic epithelial cells, showing that their expression was not different during the estrous cycle. There was also no significant difference in thymic weight and total number of thymocytes during the estrous cycle. To determine the degree of thymocyte differentiation during the estrous cycle, we analyzed thymocytes by flow cytometry. As a result, the percentage of CD4+CD8+ double-positive (DP) T cells was significantly decreased in the proestrous phase compared to the diestrous phase. However, CD4+CD8- or CD4-CD8+ (SP) T cells were significantly increased in the proestrous phase compared to the diestrous phase. In addition, the percentage of CD44+CD25- (DN1) T cells was significantly decreased in the estrous phase compared to other phases, whereas the percentages of CD44+CD25+ (DN2), CD44-CD25+ (DN3), and CD44-CD25- (DN4) were not changed during the estrous cycle. These results indicate that the development of thymocytes may arrest in the DP to SP transition stage in the proestrous phase displaying the highest serum level of estradiol. This study suggests that a change in estradiol levels during the estrous cycle may be involved in the regulation of thymocyte differentiation in the mouse thymus.